Surgery simulators in field of medical expertise and application - Polat, Ramazan; Çinar, Ahmet; Gülten, Arif (My University, 2010)
Virtual reality simulators are becoming an important tool in the education of surgeons and medicine students. Methods and procedures can be practiced before conducting surgical operations on human subjects. In this paper, the role of surgery simulators is highlighted and the efficient ways to implement a surgery simulator were investigated. ©2010 IEEE.
Tibbi e?itimde ve uygulamada cerrahi simülatörler
2010 15th National Biomedical Engineering Meeting, BIYOMUT2010 -- 21 April 2010 through 24 April 2010 -- Antalya -- 80917
Keywords: Medicine; Simulators; Surgery; Teaching; Virtual reality; Human subjects; In-field; Surgery Simulator; Surgical operation; Virtual reality simulator; Surgical equipment